Facile synthesis and ethanol sensing performance of the SnO2 nanoplates. Issue 1 (1st November 2022) - Li, Xiang-Hu; Jin, Zhen; Li, Dan; Zhang, Huan; Xu, Min-Da
Abstract: as concluded that the SnO2 nanoplates were synthesized. We characterized the material with XRD, SEM and TEM. It was concluded that the SnO2 nanoplates have good crystallinity, and the size of which is about 5μm. The SnO2 nanoplates exhibit good sensing performance in ethanol detection. There is a lower correct operating temperature (250 °C). And, in a large range of 5-500 ppm, the SnO2 nanoplates display excellent linear sensing performance in ethanol detection. The as-prepared SnO2 nanoplates have superior sensing performance in ethanol detection, such as more rapid response, better repeatability and better sensitivity. Moreover, compared with commercial SnO2 powders, it is expected that the SnO2 nanoplates might become a standout gas sensing material and it owns close relations with the application of actual production and life.